Finance and Development, June 1984. (Finance and Development; Finance and Development, 1984)
The role of the World Bank in a changing financial environment is discussed. The World Bank has made several notable changes in its financial structure and operations to assure its continuing financial strength in changing circumstances. Both the front-end fee and the variable lending rate system permit the Bank to pass through to borrowers the consequences of adverse interest rate movements. The Bank's new financial policy has significantly increased its flexibility and reduced its vulnerability to financial turbulence.